Kearifan Lokal Siri’ Na Pacce’ Dalam Perspektif Moralitas Ekonomi Pada Pedagang Kaki Lima Anjungan Pantai Losari - Damayanti, Damayanti; Muh. Syata, Wahyu; Fatchuroji, Acep (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
This research was conducted to find out the local wisdom of siri' na pacce' in the perspective of economic morality in street vendors at the Losari Beach Pavilion. Qualitative research with an ethnographic approach is the method used in this study because it analyzes a culture. Data collection was carried out by observation, in-depth interviews, and documentation studies with informants of street vendors who trade at the Losari Beach Pavilion. The analysis is carried out in three stages, namely data condentation, data presentation, and data verification. The results of the data analysis show that there is economic morality with the perspective of local wisdom of siri' na pacce' in the Bugis-Makassar tribe. This attitude of morality consists of honesty, caring for others, and shame. The implications of these three moral attitudes are obedience to economic institutions, the existence of controllers or reminders, and the reduction of economic disparities between fellow street vendors at the Losari Beach Pavilion.